2012
DOI: 10.26719/2012.18.11.1097
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of invasive bacterial diseases in children in Casablanca, Morocco: antimicrobial susceptibilities and serotype distribution

Abstract: The aim of this prospective study in Morocco was to investigate the causes of invasive bacterial diseases in children in order to inform antibiotic therapy and vaccine choices. Of 238 children aged ≤ 5 years admitted to the Children's Hospital of Casablanca for invasive diseases over a 12-month period, 185 were diagnosed with bacterial infection: 76 had chest-X-ray-confirmed pneumonia, 59 had meningitis and 50 had sepsis. Streptococcus pneumoniae was the most common pathogen identified (n = 24), followed by Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 14 publications
0
14
3
Order By: Relevance
“…Amoxicillin-resistant strains of N. meningitidis in this study were 5.6%. Whereas in previous studies at the local researches, no strains were found to be resistant to amoxicillin, while the N. meningitidis DSPG level is 9.3% in this study, which has changed over time in relation to these researches [19,20]. Thus, the resistance reported here remained less severe than those reported elsewhere [18,20].…”
Section: Co-resistance To Pg and Other Antibiotics (Table 4)contrasting
confidence: 74%
“…Amoxicillin-resistant strains of N. meningitidis in this study were 5.6%. Whereas in previous studies at the local researches, no strains were found to be resistant to amoxicillin, while the N. meningitidis DSPG level is 9.3% in this study, which has changed over time in relation to these researches [19,20]. Thus, the resistance reported here remained less severe than those reported elsewhere [18,20].…”
Section: Co-resistance To Pg and Other Antibiotics (Table 4)contrasting
confidence: 74%
“…Susceptibility from common circulating respiratory bacteria to commonly used antibiotics remains reasonably high, a finding that differs from previous reports in Moroccan ARI isolates [ 24 , 25 ]. A major limitation of this study is that the incidence of invasive bacterial disease detected among recruited patients was low (24/690; 3.5%) and of multiple etiologies, thus not allowing us to investigate susceptibility patterns among invasive isolates.…”
Section: Resultscontrasting
confidence: 97%
“…Possibly in relation to this, the proportion of total pediatric deaths attributable to pneumonia is believed to have decreased from 18% to 15% in the period of 2000 to 2012 [ 23 ], but the major gaps in knowledge regarding the precise etiology and epidemiology of pneumonia in Morocco remain inadequately addressed. Data on antibiotic susceptibility in Morocco are limited and disaggregated, although have suggested increasing trends of resistance or even multiresistance from S. pneumoniae isolates to penicillin or other commonly used antibiotics [ 24 , 25 , 26 ]. Data on antibiotic usage for respiratory infections are also scarce, although a recent survey conducted by the public health department reports that 56.5% of the approximately 130,000 children seen in primary health care settings with respiratory tract infections received antibiotics [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…No pneumococcal conjugate vaccines were introduced in Mozambique and Morocco during the study period. The burden of Hib invasive disease in Mozambique is well documented and high [16] while very scarce data on its incidence or impact are available in Morocco [17]. …”
Section: Methodsmentioning
confidence: 99%